Care and access to family planning in times of the COVID-19 pandemic C.S. Puerto Supe, 2021 - Paredes-Cruz, Elizabeth (2023)
Introduction: The COVID-19 pandemic has caused changes in health care worldwide, affecting family planning services and generating an unfavorable impact on Sexual and Reproductive Health.Objective: To describe the access and perception of family planning care during the COVID19 pandemic at the Health Center (C.S.) of Puerto Supe.Materials and Methods: Descriptive, quantitative, cross-sectional, non-experimental design of a basic type, with three study variables, user characteristics, access and perception of family planning care. We worked with the entire population, 211 users who met the inclusion criteria, users of childbearing age of legal age with complete personal data, without applying sampling because the population was small. The technique used was a survey, with a questionnaire as an instrument prior to the application of informed consent. The results were analyzed using Microsoft Excel.Results: In relation to access, 73.9% knew the means of family planning care, 92.4% obtained information about the methods from a trained professional, 98.1% acquired the contraceptive methods in the health establishment, the 88.6% of the consultations were blended, in addition, 42.6% changed or discontinued their contraceptive method, mainly due to fear of contagion 32.1%, 24.3% discontinued their contraceptive method due to lack of care or Ignorance of this, the most used method was the monthly injectable 33.6%. Regarding the general perception of family planning care, it was good in 87.1%, as well as in all its dimensions; however, responsiveness was the dimension with the highest percentage of bad evaluation at 20.9%.Conclusions: Access and perception of family planning were favorable in general terms, however, there were aspects that needed to be reinforced.